Study of temperature dependence of light yield from NaBi(WO4)2 crystals; Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment; Vol. 350, iss. 1-2 - Amosov C. Yu.; Kalinin B. N.; Krechetov Yu. F. Yuri Fedorovich; Moiseenko A. V. Aleksandr Vladimirovich; Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Sarytchev V. P.; Shuvalov E. N. Evgeny Nikolaevich; Vznuzdaev Ye. A.; Samsonov V. M.; Solodov J. P. (1994, 1994)
Title screen